Однородные решения трехмерных задач о распространении гармонических волн в транстропных термоупругих пластинах - Алтухов, Е.В.; Шевченко, В.П. (Видавничий дім "Академперіодика" НАН України, 2007)
Boundary-value problems of connected thermoelasticity for transtropic plates under various mechanical and thermal conditions given on their flat edges are investigated by the method of homogeneous solutions.